ANALISIS PERAN GURU DALAM MENERAPKAN PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR - Baiq Frecilia Dwi Syara; haifaturrahmah; Ineng Irma Rezkillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of teachers in implementing Project-Based Learning (PjBL) to enhance the creativity of elementary school students. The research employed a qualitative approach with a descriptive research design. The subjects of this study were a fifth-grade teacher and students at an elementary school. Data were collected through observation, interviews, and documentation. The findings indicate that teachers play roles as planners, facilitators, motivators, and evaluators in the implementation of PjBL. Students’ creativity is reflected through their ability to generate new ideas, collaborate in groups, and produce a variety of creative products. However, teachers face several challenges, including limited time, inadequate facilities, and students’ varying abilities to work independently. This study concludes that PjBL can effectively foster students’ creativity when teachers are able to manage the learning process optimally. Keywords: Teacher Role, PjBL, Creativity, Elementary School